The Implementation of a Cooling and Storage System for Bakpia Pathok Based on IoT Technology (Case Study : Bakpia Pathok 79) - Farida Arinie Soelistianto; Dianthy Marya; Tiara Ajeng Pamungkas (West Science Interdisciplinary Studies, 2024)
Bakpia Pathok 79, a food product made from flour, has a short shelf life and faces challenges in maintaining quality due to inadequate storage and conventional cooling methods. This study aims to design a temperature control and spoilage detection system for Bakpia Pathok 79 using gas sensors and the DHT-22 temperature sensor. Over a 6-day test period, results indicated that bakpia is best consumed immediately after cooling and remains optimal until the fourth day. In showcase 1, the MQ4 sensor detected methane levels below 195 ppm, and the MQ3 sensor detected ethanol levels below 300 ppm. In showcase 2, the MQ4 readings were below 200 ppm, and the MQ3 readings were below 260 ppm. The highest temperature of bakpia before cooling was 32°C, stabilizing at 29°C within 7 minutes. The system connects to an Android application for real-time temperature monitoring and spoilage detection, providing notifications when the bakpia is ready for packaging. Test results show the system is effective in detecting spoilage and accurately monitoring temperature.